Variations of L1 use in the English Language Class - Darmi, R; Puteh-Behak, F; Abdulllah, H; Darmi, R; Wahi, W (Penerbit Univ Kebangsaan Malaysia, 2024)
The use of the first language (L1) has been a debatable topic in the area of English language teaching. In Malaysia, the emphasis on the 'English only' approach in English language classes is still a common belief among many Malaysian ESL teachers. However, the reality is that this does not happen completely among local university students, especially in speaking skill. Thus, this paper aims to investigate the variations of L1 use, in this case Bahasa Malaysia (BM), in an English language class among university students. The study employs a qualitative approach, in which 14 participants were observed. Data gathered were analysed thematically. The findings show that generally, L1 is used by the participants for purposes reported in the literature. However, four main purposes are emphasized - task management, interpersonal use, language and content management. However, there are variations of L1 use in each category. The result provides clear justification for the need of the L1 use among university students, especially for speaking skill and that its can help build learners' confidence in improving their L2. Pedagogically, teachers need to consider learners' linguistic and cultural background in task design and allow L1 use when necessary. Without L1 use, English language learning can be discouraging for learners as it may lead to incomprehensible input. Thus, teachers have an important responsibility to design materials based on different background of learners, and be prepared for use of L1 especially among low proficiency L2 learners.